2020
DOI: 10.26480/trab.02.2020.57.60
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pinching on Yield and Yield Attributing Characteristics of Marigold (Tagetes Erecta L.): A Review

Abstract: Marigold species are famous around the world and grown for its different purpose like beautification, to extract pharmaceuticals products, loose flowers, and cut as well. Among the many species of marigold Tagetes erecta L. is one of the famous species grown in Nepal. Pinching in marigold is a process of increase in flower yield through the diversion of energy through breaking apical dominance in plants. Pinching increases the flower yield (96.78 q/ha) compared to non-pinching (68.78 q/ha) (Rathore et al., 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Across locations, the number of 5). Similar findings have also been reported by different researchers for the same crop (Bharathi et al, 2014;Lohar et al, 2018;Lalit et al, 2020).…”
Section: Number Of Inflorescence/plantsupporting
confidence: 91%
See 1 more Smart Citation
“…Across locations, the number of 5). Similar findings have also been reported by different researchers for the same crop (Bharathi et al, 2014;Lohar et al, 2018;Lalit et al, 2020).…”
Section: Number Of Inflorescence/plantsupporting
confidence: 91%
“…Based on locations, the highest mean xanthophyll content was obtained at Holleta (28.18 mg g -1 ) and Menagesha (28.1 mg g -1) for cultivar AVT540 (Table 4). Comparable xanthophyll contents of 20.19 mg g -1 (Lalit et al, 2020), 20.20 mg g -1 (Karuppaiah & Kumar, 2010), and 22.5 mg g -1 (Gobade et al, 2017) have also been reported for African marigold. On the other hand, the value obtained here is generally higher than the values reported by Ahmad et al (2011) and Renu et al (2017) for African marigold varieties in other countries.…”
Section: Xanthophyll Contentmentioning
confidence: 88%